Null Expletives and Embedded Clauses in Logoori. (6th May 2021) - Gluckman, John
Abstract: This article is an examination of null expletive subjects occurring in the context of an embedded clause in Logoori, a Kenyan Bantu language. Logoori morphologically distinguishes between two null CP‐linked expletive subjects in its subject‐agreement paradigm. Based on morphological, syntactic, and semantic evidence, I argue against the postulation of a null (pro)nominal element (e.g., p r o expl ). Instead, through a careful study of the properties of embedded CPs, such CP‐linked null expletives are shown to be a direct result of T agreeing with the embedded clause. The account situates the formal semantics of Logoori subject agreement in a plausible syntactic framework. I further illustrate how the account proposed for Logoori extends to other kinds of CP‐linked expletives in other languages, including other null‐subject languages, partial null‐subject languages, and non‐null‐subject languages.